Evaluating a computer-based body exposure paradigm for the treatment of body image disturbance in adolescent Anorexia Nervosa: effects on the attentional bias and emotions - Sasse, Lena; Stonawski, Valeska; Kratz, Oliver; Moll, Gunther; Horndasch, Stefanie (Frontiers in Psychology, 2024)
Background. A diagnostic criterion of Anorexia Nervosa (AN) is body image disturbance.Body exposure therapy is a widely used approach to treat this; however, it is unclear which part of body exposure therapy is relevant for regaining a realistic perspective on the own body. This study aimed to examine the role of the attentional bias (AB), which AN patients exhibit to the most disliked parts of their body. Additionally, emotional responses to the body exposure sessions were examined. Methods. Participants were adolescent girls with a diagnosis of AN, who were randomly assigned to either an intervention (INT) or a treatment-as-usual (TAU) group. Both groups completed a pre and a post session, which included the completion of questionnaires to measure AN-psychopathology. The INT group received four sessions of a computer-based body exposure between the pre and the post session. The viewing pattern was recorded before and after each intervention session via an eyetracking (ET) device, as were emotional response scores on a visual analogue scale (VAS; anxiety and disgust). The TAU group did not receive the intervention, but viewing patterns were recorded during the pre and the post session. All participants were asked to list their three least favourite body parts to be able to subsequently assess the AB. Results. 58 adolescent girls with AN participated in the study. There were no differences in psychopathology pre to post session, as measured by administered questionnaires. The existence of an AB could be replicated, but there was no significant reduction in the AB pre to post session in the INT group, nor was there an interaction between group and time. Also, no changes in the AB were found within and between sessions in the INT group. Anxiety scores reduced significantly across sessions while disgust scores were significantly higher post session than they were pre session.While the existence of an AB was demonstrated, the carried-out body exposures were neither sufficient to reduce the AB nor the psychopathology; nevertheless, a significant decrease in anxiety levels showed the usefulness of the exposure sessions. Future research might benefit from more exposure sessions and incorporating AB modification training (ABMT).